Synthesis and application of short alkanes filled microcapsules - Eng, Suky (2011)
This project synthesizes Urea-formaldehyde microcapsules containing n-tetradecane, using in situ polymerization at agitation rate of 600rpm. Both optical microscopy and scanning electron microscopy show the rough surface and that n-tetradecane migrate out of its shell resulting in flatten the microcapsules when they were exposed to temperature below its melting point. Themogravimetric Analysis and Differential Scanning Calorimetry were used to find the thermal properties of the microcapsules at room temperature in comparison to its components. Microcapsules were mixed into polyurethane to investigate the deicing properties using contact angle measurements at room temperature after warmed up from below melting point. It was concluded that with higher concentration of microcapsules in polyurethane, the polyurethane becomes more hydrophobic as the contact angle increases. Also, with higher concentration of microcapsules, droplets of water which condense on cold surface of polyurethane join together more quickly, further proving its hydrophobic characteristics.